The Needs of Virtual Machines Implementation in Private Cloud Computing Environment - Edy Kristianto (Bina Nusantara University, 2015)
The Internet of Things (IOT) becomes the purpose of the development of information and communication technology. Cloud computing has a very important role in supporting the IOT, because cloud computing allows to provide services in the form of infrastructure (IaaS), platform (PaaS), and Software (SaaS) for its users. One of the fundamental services is infrastructure as a service (IaaS). This study analyzed the requirement that there must be based on a framework of NIST to realize infrastructure as a service in the form of a virtual machine to be built in a cloud computing environment.